Classification Of Images In Ancient Greek Myths And Legends - Solijonova, Mukhtaramoy (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes Greek myths and mythological images and their distinctive features. The role and significance of myth in fiction is highlighted.